1995
DOI: 10.3928/0147-7447-19951001-09
|View full text |Cite
|
Sign up to set email alerts
|

Primary Bone Tumors of the Spine: A Survey of the Evaluation and Treatment at the Istituto Ortopedico Rizzoli

Abstract: The experience at Istituto Rizzoli with 366 primary bone tumors of the spine focuses on the criteria for planning and treatment. An accurate preoperative evaluation by standard radiograph, computerized tomography scan, and magnetic resonance imaging allow the classification of benign lesions as latent (not requiring treatment), active (curettage), or aggressive (curettage plus adjuvants or marginal resection). The malignant lesions are classified as intracompartmental or extracompartmental (both low and high g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Therefore, it is extremely difficult to investigate curative effects for primary spinal tumors (22), and the treatment principles are mostly based on a summary of experience. In a literature review, the present study found only five large case reports on primary spinal tumors (4,7,20,23,24). The sex ratios were 1:1, the mean ages were 55, 42, 43, 45, and 48 years, respectively, and the proportions of malignant tumors was 86%, 43%, 49%, 39%, and 100% respectively.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Therefore, it is extremely difficult to investigate curative effects for primary spinal tumors (22), and the treatment principles are mostly based on a summary of experience. In a literature review, the present study found only five large case reports on primary spinal tumors (4,7,20,23,24). The sex ratios were 1:1, the mean ages were 55, 42, 43, 45, and 48 years, respectively, and the proportions of malignant tumors was 86%, 43%, 49%, 39%, and 100% respectively.…”
Section: Discussionmentioning
confidence: 71%
“…Although the incidence of primary cervical spinal tumors is low, the mortality and disability rates are high (5), especially among young patients (6). The main causes of death or disability in affected patients are local tumor invasion of adjacent structures, nerve damage caused by nerve compression, and systemic metastasis (7). Owing to the extremely low incidence rate, current treatments are mostly based on case series studies and summaries, and lack highquality evidence (5,(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Boriani et al [6] described three major methods of performing en bloc excisions in the thoracolumbar spine: vertebrectomy if the tumor is confined to zones 4 to 8 or 5 to 9; sagittal resection when the tumor occupies zones 3 to 5 or 8 to 10 and resection of the posterior arch when it is located between the zones 10 and 3 according to their surgical staging system. However, en bloc resection is a highly demanding procedure that must be carefully planned and the greater surgical risk can be accepted only if it offers a safer result and is performed by specialized surgical and anesthesiology teams [5].…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic goal is a complete tumor removal and spinal column stability restoration [1]. The publications of Weinstein, Boriani and Biagini and their surgical staging system (WBB) have been of great interest in this field [5][6]. We report a rare localization of solitary thoracic EWS in an adult patient that was treated with en bloc vertebrectomy.…”
Section: Introductionmentioning
confidence: 99%
“…However, en bloc resection is a highly demanding procedure that must be carefully planned and the greater surgical risk can be accepted only if it offers a safer result and is performed by specialized surgical and anesthesiology teams 5 …”
Section: Discussionmentioning
confidence: 99%